Superwettable and injectable GelMA-MSC microspheres promote cartilage repair in temporomandibular joints - Yang, Yue; Huang, Chenyan; Zheng, Huimin; Meng, Zhaoqiang; Heng, Boon Chin; Zhou, Tuanfeng; Jiang, Shengjie; Wei, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
Abstract: Temporomandibular disorders (TMD) can be treated by promoting cartilage regeneration with biomaterials. However, there are deficiencies in the infiltration function of bone filler biological materials. In this study, stems cells were loaded onto gelatin methacryloyl (GelMA) hydrogel microspheres endowed with superwettable properties and TGF-β sustained-release function, which can quickly infiltrate the irregular surface of the temporomandibular joint (TMJ) bone defect area and accelerate cartilage defect healing. First, to improve cell adhesion and spreading function, the BMSCs-coated GelMA microspheres were endowed with superwetting property. At the same time, the swelling adsorption characteristics of gelatin microspheres could be used to load recombinant TGF-β within the microspheres, which could in turn promote the chondrogenic differentiation of multi-potent bone marrow mesenchymal stem cells. The SEM imaging demonstrated that BMSCs-coated GelMA microsphere has superwettable and superhydrophilic problems, which enabled rapid adaptation to the bone defect surface morphology, which is conducive to tissue repair. Furthermore, the cartilage defect model showed that rBMSCs-coated GelMA microspheres promote temporomandibular joint arthritis repair. In conclusion, our study established that BMSC-coated GelMA microspheres endowed with superwetting properties, can colonize the bone defect repair site better with sustained release of growth factors, thus providing an innovative strategy for promoting cartilage regeneration.